THU0552 Haplotypes of Vitamin D Receptor Gene: Both Risky and Protective for Fibromiyalgia (FMS). (15th July 2016) - Balkarli, A.; Akyol, M.; Tepeli, E.; Balkarlı, H.; Temel, S.; Cobankara, V.
Abstract : Background: Clinical observations suggest that vitamin D may influence fibromyalgia etiology. FMS and vitamin D deficiency share a similar symptom profile; the relationship between these conditions is unclear. Vitamin D receptor is a crucial mediator of the symptoms of vitamin D deficiency. Thus, vitamin D receptor gene polymorphisms or haplotypes may contribute to vitamin D resistance. Objectives: This study evaluated the clinical relationship between FMS and vitamin D gene among Turkish FMS patients. Methods: 73 patients with FMS were diagnosed according to the ACR 2010 criteria; the control group included 61 healthy unrelated volunteers. The rs2228570 (Fok I), rs1544410 (Bsm I), rs7975232 (Apa I) and (rs731236) Taq I polymorphisms were examined using PCR-RFLP. Results: In individual SNP analyses, none of the snps have been found to be associated with FMS (p values are 0.491, 0.477, 0.207, and 0.736 respectively). However, it has been detected that there is a strong association between haplotypes of VDR gene polymorphisms and FMS. As a result of this study, the effect of haplotypes is shown to be both risky and protective. P value of risk haplotypes ATC (rs2228570, rs1544410, rs7975232) is 0, 015 (26, 5%) and TTT is 0, 0068 (12, 8%). The p value of collected risk haplotypes (ATC, TTT) is 0, 006 (39, 3%) and (ATC, TGT, and TTT) 0, 000009 (58, 7%). Frequent protective haplotype TTC is 0, 0385 (6, 8%). The p value of collected protective haplotypes (ATT, TCG, and TTC) is 0, 008 (38%). Conclusions: The present study is the first study evaluating VDR gene in patients with FMS. Our results suggest that haplotypes in VDR are strongly associated with fibromyalgia expressing both risk and protective effect. Our findings may help guide future research needed to define the role of vitamin D in FMS. Disclosure of Interest: None declared